Network analysis of the associations between personality traits, cognitive functioning, and inflammatory markers in elderly individuals without dementia - Bastelica, Thomas; Lespine, Louis-Ferdinand; Rouch, Isabelle; Tadri, Myriam; Dorey, Jean-Michel; Strippoli, Marie-Pierre F.; d'Amato, Thierry; von Gunten, Armin; Preisig, Martin; Rey, Romain (Frontiers in Aging Neuroscience, 2023)
Introduction Lower cognitive functioning in old age has been associated with personality traits or systemic inflammatory markers. Associations have also been found between personality traits and inflammatory markers. However, no study has explored the inter-relationships between these three components simultaneously. The present study aims to better understand the inter-relationships among personality traits, inflammatory markers, and cognitive performance in elderly individuals without dementia. Methods This study utilizes a network analysis approach, a statistical method that allows visualization of the data’s unique pairwise associations. We performed a cross-sectional analysis on 720 elderly individuals without dementia, using data from Colaus|PsyColaus, a population-based study conducted in Lausanne, Switzerland. The Revised NEO Five-Factor Inventory (NEO-FFI-R) was used to assess personality traits, and interleukin (IL)-1β, IL-6, tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP) were used as peripheral inflammatory markers. Cognitive domains were investigated using the Mini-Mental State Examination (MMSE), the Verbal Fluency Test, the Stroop Test, the DO40, and the Free and Cued Selective Reminding (FCSR) test. Results Openness was associated with verbal fluency and Agreeableness with immediate free recall. In contrast, no association between inflammatory markers and personality traits or cognition was identified. Discussion In elderly individuals without dementia, a high level of Openness or Agreeableness was associated with executive functioning/semantic memory and episodic memory, respectively.